Application of Subcontractor Selection Using Analytical Hierarchy Process Method in Ritz Garment - Ramadhani , Muthia; Handayati, Yuanita (KnE Social Sciences, 2020)
This research was conducted in Ritz Garment to determine the level of importance of the criteria and sub-criteria that are used for subcontractor selection for Ritz Garment, assess the performance of current and alternative subcontractors, and provide recommendations for Ritz Garment based on the subcontractor selection. To determine the importance of the criteria and sub-criteria and also to score alternatives towards each of the sub-criteria, decision-makers which are the manager and owner of Ritz Garment are interviewed as respondents to get their expert judgment. The interview will generate pairwise comparison for each criterion and sub-criteria from each respondent that will be averaged using geometric mean to get the numbers that will be used to calculate the weight of each criteria and sub-criteria. From the result of this research that is conducted using AHP method with the Expert Choice software, level of importance for each criterion and alternatives are obtained. The order of importance of criteria is Quality (0.296), Cost (0.290), Reliability (0.273), Delivery (0.080), and Flexibility (0.061). The sequence for sub-criteria Global Weight is Defect Rate (0.156), Trustworthy (0.154), Internal Cost (0.153), Conformance Quality (0.140), Product Price (0.137), Product Reliability (0.119), Customization (0.051), Compliance with Quantity (0.045), Compliance with Schedule (0.035), and Product Volume Changes (0.010). For the alternatives, the order of importance is Alternative Subcontractor 1 (7.667), Alternative Subcontractor 2 (0.7.314), Alternative Subcontractor 3 (7.099) and Current Subcontractor (6.266). From the result, it is concluded that Alternative Subcontractor 1 is the best subcontractor to replace Current Subcontractor. Keywords: garment industry, subcontractor selection, analytical hierarchy process, criteria, sub-criteria, best subcontractor, case study